2016
DOI: 10.1016/j.jpeds.2015.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Treatment of Intestinal Rotational Abnormalities in Heterotaxy: A Systematic Review and Meta-Analysis

Abstract: The screen-detected incidences of IRA and acute midgut volvulus were significantly greater in heterotaxy than the normal population. Prophylactic Ladd procedure was associated with less morbidity and mortality compared with emergency surgery. A long-term prospective randomized trial is needed to define the indication for screening and prophylactic treatment of IRA in heterotaxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Intestinal malrotation increases the risk of midgut volvulus, which can potentially result in significant bowel loss, intestinal insufficiency and death 52,53 . A recent systematic review 54 exploring the association between intestinal malrotation and heterotaxy reported a prevalence of 58% (95% CI, 36-78%) in children with heterotaxy undergoing screening for bowel anomalies, although there was wide heterogeneity in screening regimens among the included studies. In the present review, intestinal malrotation occurred in 14.2% and 27.1% of cases with LAI and RAI, respectively.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal malrotation increases the risk of midgut volvulus, which can potentially result in significant bowel loss, intestinal insufficiency and death 52,53 . A recent systematic review 54 exploring the association between intestinal malrotation and heterotaxy reported a prevalence of 58% (95% CI, 36-78%) in children with heterotaxy undergoing screening for bowel anomalies, although there was wide heterogeneity in screening regimens among the included studies. In the present review, intestinal malrotation occurred in 14.2% and 27.1% of cases with LAI and RAI, respectively.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Associated major cardiac anomalies are the main determinant in anticipating the outcome for children affected by heterotaxy; however, even those presenting with isolated defects can experience short-and long-term morbidity such as intestinal malrotation, biliary atresia and respiratory and immune disorders [6][7][8][9] . Assessment of the thoracoabdominal situs is an integral part of the sonographic screening examination of the fetal heart and has led to an increase in the prenatal diagnosis of heterotaxy 10 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6,13,14 The authors of two recent systematic reviews report similar results. 15,16 The first included 11 heterogeneous retrospective studies of 649 patients with HS. 15 Of the 44% of patients who were screened, 47% had IRA.…”
Section: Discussionmentioning
confidence: 99%
“…The second meta-analysis (24 studies, including 1433 patients with HS) suffers from similar limitations as Landisch et al 15 with heterogeneity in reporting overall incidence of IRA, detection rate of IRA after screening asymptomatic cases, prevalence of volvulus, and surgical complications. 16 It reports a 58% incidence of IRA in screened patients. Both reviews report higher risks of perioperative complications than that of volvulus.…”
Section: Discussionmentioning
confidence: 99%
“…High mortality (18%) was reported after the emergency Ladd procedure for intestinal malrotation with heterotaxy [7]. On the other hand, neonates with infracardiac TAPVC presenting severe hypoxia and acidosis should be immediately taken to the operating room [1].…”
Section: Discussionmentioning
confidence: 99%